2008
DOI: 10.1038/nn.2136
|View full text |Cite
|
Sign up to set email alerts
|

Absolute requirement of GDNF for adult catecholaminergic neuron survival

Abstract: GDNF is a potent neurotrophic factor that protects catecholaminergic neurons from toxic damage and induces fiber outgrowth. However, the actual role of endogenous GDNF in the normal adult brain is unknown, even though GDNF-based therapies are considered promising for neurodegenerative disorders. We have generated a conditional GDNF-null mouse to suppress GDNF expression in adulthood, hence avoiding the developmental compensatory modifications masking its true physiologic action. After Gdnf ablation, mice showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
244
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 300 publications
(262 citation statements)
references
References 42 publications
16
244
1
1
Order By: Relevance
“…GDNF may be involved in postnatal DA SNpc maintenance (Kopra et al, 2015; Pascual & López‐Barneo, 2015; Pascual et al, 2008). Although FS are the main producers of striatal GDNF, ACh marginally contribute to its expression (Hidalgo‐Figueroa et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…GDNF may be involved in postnatal DA SNpc maintenance (Kopra et al, 2015; Pascual & López‐Barneo, 2015; Pascual et al, 2008). Although FS are the main producers of striatal GDNF, ACh marginally contribute to its expression (Hidalgo‐Figueroa et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…We define three parallel and interdependent neurotrophic relationships characterized by (a) a bidirectional relation between DA SNpc and FS which may involve GDNF (Hidalgo‐Figueroa et al, 2012; Kopra et al, 2015; Pascual & López‐Barneo, 2015; Pascual et al, 2008); (b) a unidirectional relation between ACh and DA SNpc that does not involve GDNF; and (c) a dependence of ACh survival on Shh that not exclusively requires the DA SNpc but may imply FS and ACh (Figure 5d).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GDNF exerts its effects by regulating cell survival and cell differentiation through PI3K/Akt and Ras/ERK pathways (Toth et al, 2002). The potential neuroprotection and neurorestoration effects of GDNF have been examined in both rodent and nonhuman primate models of PD with positive effects shown in a variety of them Eslamboli et al, 2003;Pascual et al, 2008). These encouraging results then prompted initial open-label clinical trials, which suggested that continuous delivery of GDNF (or its relative, neurturin) by protein infusion or viral vectormediated delivery was efficacious in advanced PD patients (Gill et al, 2003;Marks et al, 2008).…”
Section: Introductionmentioning
confidence: 99%